Hill-Sachs Lesion: Diagnosis, Classification, and Treatment - Tamaoki, Marcel Jun Sugawara; Utino, Artur Yudi; Zan, Renato Aroca; Matsunaga, Fabio Teruo; Archetti Netto, Nicola (Revista Brasileira de Ortopedia, 2025)
A lesão de Hill-Sachs é uma condição frequentemente associada à instabilidade anterior do ombro, que desempenha um papel crucial nos resultados de seu tratamento The Hill-Sachs lesion is a condition frequently associated with anterior shoulder instability, which plays a crucial role in the outcomes of its treatment. It is characterized by a posterior compressive fracture in the humeral head caused by an impingement against the anterior rim of the glenoid cavity during dislocation. A thorough understanding of this lesion is essential to support clinical decisions and choose the most appropriate treatment. Advances in imaging modalities, such as magnetic resonance imaging and computed tomography, enabled lesion identification with greater precision and its classification per depth, location, and volume, resulting in a detailed assessment of its role in shoulder instability. The present article reviews the main classifications, diagnostic methods, and treatment options to provide orthopedists with a comprehensive and updated view of the strategies to promote better functional outcomes and minimize the risk of instability recurrence.
Keywords: humeral fractures; joint instability; orthopedic procedures; shoulder dislocation